2023
DOI: 10.1155/2023/8429106
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Method Based on the FIPV N Monoclonal Antibody Immunofluorescence Assay and RT-nPCR Method for the Rapid Diagnosis of FIP-Suspected Ascites

Abstract: Feline infectious peritonitis (FIP), which is caused by feline infectious peritonitis virus (FIPV), is a fatal and immunologically mediated infectious disease among cats. At present, due to the atypical clinical symptoms and clinicopathological changes, the clinical diagnosis of FIP is still difficult. The gold standard method for the differential diagnosis of FIP is immunohistochemistry (IHC) which is time-consuming and requires specialized personnel and equipment. Therefore, a rapid and accurate clinical dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Both type I and type II FCoV can occur as less-virulent FCoV and as FIP-associated FCoV [ 9 ]. Type I FCoV is more prevalent in most parts of the world [ 16 , 58 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]; a prevalence of type I of 80–95% has been reported [ 75 , 76 ].…”
Section: Agent Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both type I and type II FCoV can occur as less-virulent FCoV and as FIP-associated FCoV [ 9 ]. Type I FCoV is more prevalent in most parts of the world [ 16 , 58 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]; a prevalence of type I of 80–95% has been reported [ 75 , 76 ].…”
Section: Agent Propertiesmentioning
confidence: 99%
“…Both studies concluded that a combination of both FCoV RT-PCR and antibody testing would be more helpful to support a diagnosis of FIP compared to either test alone [ 301 , 326 ]. Similarly, one study described the success of combining a newly developed FCoV N-gene IFA test with FCoV RNA RT-PCR testing on effusions for the diagnosis of FIP [ 69 ].…”
Section: Diagnosis Of Fipmentioning
confidence: 99%